2(3x-3)+2(x-3)=(2x-1)+(2x+1)+2x

Simple and best practice solution for 2(3x-3)+2(x-3)=(2x-1)+(2x+1)+2x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(3x-3)+2(x-3)=(2x-1)+(2x+1)+2x equation:


Simplifying
2(3x + -3) + 2(x + -3) = (2x + -1) + (2x + 1) + 2x

Reorder the terms:
2(-3 + 3x) + 2(x + -3) = (2x + -1) + (2x + 1) + 2x
(-3 * 2 + 3x * 2) + 2(x + -3) = (2x + -1) + (2x + 1) + 2x
(-6 + 6x) + 2(x + -3) = (2x + -1) + (2x + 1) + 2x

Reorder the terms:
-6 + 6x + 2(-3 + x) = (2x + -1) + (2x + 1) + 2x
-6 + 6x + (-3 * 2 + x * 2) = (2x + -1) + (2x + 1) + 2x
-6 + 6x + (-6 + 2x) = (2x + -1) + (2x + 1) + 2x

Reorder the terms:
-6 + -6 + 6x + 2x = (2x + -1) + (2x + 1) + 2x

Combine like terms: -6 + -6 = -12
-12 + 6x + 2x = (2x + -1) + (2x + 1) + 2x

Combine like terms: 6x + 2x = 8x
-12 + 8x = (2x + -1) + (2x + 1) + 2x

Reorder the terms:
-12 + 8x = (-1 + 2x) + (2x + 1) + 2x

Remove parenthesis around (-1 + 2x)
-12 + 8x = -1 + 2x + (2x + 1) + 2x

Reorder the terms:
-12 + 8x = -1 + 2x + (1 + 2x) + 2x

Remove parenthesis around (1 + 2x)
-12 + 8x = -1 + 2x + 1 + 2x + 2x

Reorder the terms:
-12 + 8x = -1 + 1 + 2x + 2x + 2x

Combine like terms: -1 + 1 = 0
-12 + 8x = 0 + 2x + 2x + 2x
-12 + 8x = 2x + 2x + 2x

Combine like terms: 2x + 2x = 4x
-12 + 8x = 4x + 2x

Combine like terms: 4x + 2x = 6x
-12 + 8x = 6x

Solving
-12 + 8x = 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
-12 + 8x + -6x = 6x + -6x

Combine like terms: 8x + -6x = 2x
-12 + 2x = 6x + -6x

Combine like terms: 6x + -6x = 0
-12 + 2x = 0

Add '12' to each side of the equation.
-12 + 12 + 2x = 0 + 12

Combine like terms: -12 + 12 = 0
0 + 2x = 0 + 12
2x = 0 + 12

Combine like terms: 0 + 12 = 12
2x = 12

Divide each side by '2'.
x = 6

Simplifying
x = 6

See similar equations:

| 7=-v-3+6 | | 4(b-2)=(5-b) | | (x+55)+(3x-5)=90 | | 4r^2-r=0 | | 6,5x-9=10,5 | | 2.5d=3 | | 2=5r-3r | | 4q+8=5y | | 6x-2(x+3)=5x-1(+2) | | -6x+5(5x+12)=-168 | | 5y+12x+6=0 | | p-4=-9+9 | | 26-(3x+2)= | | 5x-17=2x+10 | | 22=11k | | 14-x=48 | | 2c-3+9d+7-6d= | | x+(x-26)=180 | | 1h+1+2h+1=6h+6-1h+2 | | 5+9y=5y+5 | | x(y-3)=40 | | 5x+4=23 | | 2c/11=(c-3)/4 | | 8=-2x+4-2 | | 2x-1=24.5 | | 5+x=5y+5 | | x^2-10x+10= | | 2c/11=c-3/4 | | 6+3x=11-2x | | 256=6x-4(-4x-20) | | 9y+5=5y | | k-76.98=43.56 |

Equations solver categories